Managing news nerds: strategizing about institutional change in the news industry. Issue 1 (2nd January 2020) - Kosterich, Allie
ABSTRACT: Technological developments, along with associated economic realities and social changes, continue to disrupt current practices of the news media industry, which creates substantial impacts on news firm management strategy and performance. This research is an exploratory step in understanding the strategies related to institutional change within the context of the news media industry, specifically as related to change in the journalist profession and the rise of news nerds. Using semi-structured interviews with 20 news editors and managers across 17 news firms (global and local within the United States), I examine patterns of strategies and how they relate to institutional change within the journalist profession and the news media industry more broadly. The findings from this research answer questions about the strategies that drive rapid institutional change in the journalist profession.